Estimation of the potential of understorey and litter carbon on the shrub bush vegetation in Aceh Besar District. Issue 1 (January 2021) - Umar, U; Sufardi, S; Syafruddin, S; Teti, T; Munar, M
Abstract: The distribution of shrub vegetation is almost evenly distributed in Aceh Besar district. The desire to see the carbon potential in this vegetation and treat it - future treatment will be carried out both reforestation and soil management to increase carbon stock for the future. Therefore, it is necessary to research and determine how much carbon potential is in scrub vegetation in the district Aceh Besar by making plots according to field conditions. Then, decided each vegetation growth on seedling plot sizes with a minimum area of 4 m2 (growth rate woody vegetation < 2 cm in diameter with a height = 1.5 m) and minimal stake plot area 25 m 2 (growth rate of woody vegetation with a diameter of 2 cm to <10 cm). Each plot, both seedling and sapling plots, was repeated five times. Vegetation Shrubs <2 cm in size are dominated by Teki grass ( Cyperus rotundus ) and Putri Malu ( Mimosa pudica ). For shrub, vegetation measures 2 cm - 10 cm across dominance by Acacia mangium plants. The total amount of plant carbon biomass is 2, 053, 546.33 tonnes/ha, a C value of 964, 990.26 tonnes/ha, and the potential for CO2 absorption at plants amounting to 3, 540, 455.15 tonnes/ha on shrub vegetation in the district Aceh Besar.